1975
DOI: 10.1039/f29757101913
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron studies of metal carbonyls. Part 5.—Substituted group VIIA carbonyls

Abstract: The He I and He I1 spectra of the compounds M(CO)5X and M2COlo (M = Mn, Re ; X = C1, Br, I), valence region X-ray photoelectron spectra of M2(CO)lo, and the He I spectra of some related compounds are reported and discussed. From observations of intensity changes it is deduced that in M(CO)51 and Re(CO),Br the orbital ionisation sequence for the low ionisation potential region is e(X) < b,(M) < e(M) < al(M-X Q bonding), but that in M(CO),C1 and Mn(CO),Br the sequence of e orbital ionization potentials is revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
18
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 1 publication
8
18
0
Order By: Relevance
“…This is in good agreement with published PE spectra of LMn(CO)5 and LRe(CO)3 with L = H, CH3, X [40][41][42],…”
Section: M[mn(co)5]2supporting
confidence: 81%
“…This is in good agreement with published PE spectra of LMn(CO)5 and LRe(CO)3 with L = H, CH3, X [40][41][42],…”
Section: M[mn(co)5]2supporting
confidence: 81%
“…Bands (2) and (4) have comparable cross sections. The close correspondence between measured intensities and localization properties of the orbital wavefunctions is well known in photoelectron spectroscopy of transition metal compounds [34,35]. The substituent effects are in line with the assumption that band (5) is due to an ionization event from an MO with a large rr contribution.…”
Section: 'supporting
confidence: 57%
“…The smaller shift in the Re series compared to the Mn series is also expected since we expect in the corresponding orbital in 4-6 less metal character than in 1-3 due to the better overlap between ~'1 and the Re 5d functions compared with the Mn 3d functions. In the assignment of the ionization potentials of 4-6 we have neglected the effects of spin-orbit coupling in the 5d shell although previous studies on highly symmetrical 5d complexes have shown that the positions of the bands are influenced by spin-orbit interactions [35][36][37][38][39]. Significant shifts, however, have been found only in transition metal complexes with spatially degenerate MO and small metal ligand overlap.…”
Section: 'mentioning
confidence: 94%
“…The electronic structure of manganese pentacarbonyl halides has been the subject of many theoretical, 9,10 ultraviolet photoelectron spectroscopic (UPS), [11][12][13][14][15][16] and UV-vis spectroscopic studies. 7,[17][18][19] For the present purpose in particular the molecular orbital structure and the excitation spectrum are relevant and will be discussed in section 3.…”
Section: Introductionmentioning
confidence: 99%